CHARACTERISTICS OF THE USE OF METAPHORICAL AND PHRASEOLOGICAL IMAGES IN THE WORK OF ART (World Bulletin of Social Sciences, 2023)
This article discusses the direction of linguoculturology of modern linguistics, the linguocultural features of the work “Shaytanat”,national units, their peculiarities.